Anti-diabetic Potential of a Stigmasterol From the Seaweed Gelidium spinosum and Its Application in the Formulation of Nanoemulsion Conjugate for the Development of Functional Biscuits - Poulose, Navya; Sajayan, Arya; Ravindran, Amrudha; Chandran, Ambili; Priyadharshini, G. Balasubramanian; Selvin, Joseph; Kiran, G. Seghal (Frontiers in Nutrition, 2021)
The seaweed Gelidium spinosum was selected for the extraction of phytosterol by Soxhlet extraction method. The extracted phytosterol was chemically characterized as stigmasterol using FT-IR and GC-MS analysis. The antioxidant and α-amylase inhibitory activity of stigmasterol was confirmed by in vitro assays. In vivo studies demonstrated anti-diabetic effect in STZ-induced hyperglycemic rats. The biochemical assays showed administration of stigmasterol reduced the blood sugar, urea and creatinine level. Histopathology observation showed stigmasterol reduces the damage of the pancreas, liver and kidney tissues and also helped in glycogen synthesis. The stigmasterol was then nano-emulsified and was then incorporated into dough for the formulation of biscuit. The stigmasterol incorporated biscuit showed higher proximate values, low moisture content, color was lighter and the textural property revealed lower hardness. Sensorial evaluation showed much likness when compared to the control. This study demonstrated stigmasterol reduced hyperglycemic effects and thus can be used as a potential agent for diabetes treatment.